Increased Severity of Ulcerative Colitis in the Terminal Phase of the Metabolic Syndrome - Jovanovic, Marina Milun; Jurisevic, Milena Milenko; Gajovic, Nevena Miroslav; Arsenijevic, Nebojsa Nikola; Jocic, Miodrag Vukasin; Jovanovic, Ivan Petar; Zdravkovic, Natasa Dragan; Djukic, Aleksandar Ljubodrag; Maric, Veljko Jovo; Jovanovic, Milan Milorad (Tohoku journal of experimental medicine, 2021)
Ulcerative colitis is chronic immune-mediated disorder that affects primarily colonic mucosa. The metabolic syndrome has increasing global prevalence with a significant impact on biology of chronic diseases, such as ulcerative colitis. Today it is known that the metabolic syndrome attenuates severity of ulcerative colitis. Still, there is no evidence that different stages of metabolic syndrome alter the course of the ulcerative colitis. The aim of this study was to dissect out how progression of the metabolic syndrome impacted the biology of ulcerative colitis and severity of clinical presentation. Seventy-two patients (41 men and 31 women, 22-81 years old) were enrolled in this observational cross-sectional study. Concentrations of pro- and anti-inflammatory cytokines in serum and feces samples were measured and phenotype of colon infiltrating cells was analyzed. Patients in the terminal phase of the metabolic syndrome have clinically and pathohistologically more severe form of ulcerative colitis, which is followed by decreased concentrations of systemic galectin-1, increased values of systemic pro-inflammatory mediators and increased influx of lymphocytes in affected colon tissue. Our data suggest that reduced concentrations of galectin-1 and predomination of the pro-inflammatory mediators in patients with terminal stage of the metabolic syndrome enhance local chronic inflammatory response and subsequent tissue damage, and together point on important role of galectin-1 in immune response in ulcerative colitis patients with the metabolic syndrome.